A method for preparing nitrogen-doped carbon nanosheets for lithium ion battery negative electrodes from waste low-density polyethylene by atmospheric temperature gradient pyrolysis

CN122916098APending Publication Date: 2026-10-16HENAN POLYTECHNIC UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611090842.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-22
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0009]本发明的目的在于克服现有技术中存在的二维碳材料制备过程复杂、模板去除不环保、塑料热解挥发难以有效固碳、常压条件下难以构筑结构可控的碳纳米片等不足,提供一种利用废旧低密度聚乙烯(LDPE)为碳源,以石墨相氮化碳(g-C3N4)为多功能生长平台,利用废旧LDPE和g-C3N4在热分解温区上的差异,通过常压温度梯度热解制备氮掺杂多孔碳纳米片的方法

Benefits of technology

1、本发明提供了一种常压温度梯度热解废旧LDPE制备氮掺杂碳纳米片的方法,该方法利用LDPE与g-C3N4热分解温区不同的特点,实现了废旧LDPE裂解挥发物沉积碳化与g-C3N4自牺牲分解过程的分段协同耦合。与单纯将g-C3N4作为物理模板使用不同,本发明先通过500 ℃短时间保温使LDPE先裂解形成含烃挥发物、随后在700 ℃使气态产物在g-C3N4片层结构尚未完全分解前发生沉积和原位碳化,最后在800 ℃使g-C3N4自牺牲分解。该方法同步实现了模板去除、原位氮掺杂和孔结构构筑,从而在常压条件下实现废旧LDPE裂解产物向碳材料的转化。该过程避免了传统塑料热解制碳对密闭或加压反应设备的依赖;并且无需金属催化剂、外加氮源、活化处理或后纯化处理,工艺流程较短,环境友好性较好。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122916098A_ABST
    Figure CN122916098A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of carbon nanomaterial preparation and lithium ion battery negative electrode material, and relates to a method for preparing nitrogen-doped carbon nanosheets for lithium ion battery negative electrodes by pyrolyzing waste low-density polyethylene (LDPE) under normal pressure and temperature gradient. Waste LDPE powder is mixed with graphite phase carbon nitride (g-C3N4), and then one-pot pyrolysis is carried out under normal pressure and inert atmosphere. The method directly obtains nitrogen-doped carbon nanosheets through LDPE decomposition at 500 DEG C, carbon deposition of gaseous products on the surface of g-C3N4 at 700 DEG C, and self-sacrificial decomposition of the g-C3N4 template at 800 DEG C. The carbon nanosheets prepared by the method are controllable in thickness, uniform in pores, rich in defects, and can be in-situ doped with nitrogen, and exhibit excellent electrochemical performance: after 1000 cycles at a current density of 1.0 A g ‑1 -1, the capacity is still as high as 436 mAh g ‑1 -1. The application can simply convert waste plastics into carbon negative electrode materials for high-energy-density lithium ion batteries. The preparation process does not require complex pressurizing equipment, catalysts and post-purification treatment, and has the prospect of large-scale preparation and commercial application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field of carbon nanomaterial preparation and lithium-ion battery anode materials, and relates to a method for preparing nitrogen-doped carbon nanosheets for lithium-ion battery anodes by atmospheric pressure temperature gradient pyrolysis of waste low-density polyethylene; it also relates to the application of nitrogen-doped porous carbon nanosheets prepared by this method in lithium-ion battery anode materials. Background Technology

[0002] Lithium-ion batteries, due to their high energy density, long cycle life, and well-established engineering applications, have been widely used in portable electronic devices, electric vehicles, and large-scale energy storage. With the rapid development of electric vehicles and new energy storage systems, higher demands are being placed on the energy density, rate performance, and cycle life of lithium-ion batteries. As a crucial component of lithium-ion batteries, the anode material significantly impacts battery capacity, rapid charge / discharge capability, and long-term cycle stability.

[0003] Currently, graphite is the primary anode material for commercially available lithium-ion batteries. Graphite possesses a stable layered structure, good conductivity, and a mature industrial foundation, but its theoretical specific capacity is only 372 mAh g⁻¹. -1 Furthermore, under high-rate charge-discharge conditions, these materials are easily limited by lithium-ion diffusion kinetics, making it difficult to further meet the development requirements of high-energy-density and high-power-density lithium-ion batteries. Therefore, developing novel carbon-based anode materials with higher lithium storage capacity and faster ion transport capabilities is an important research direction in the current lithium-ion battery field.

[0004] Two-dimensional carbon nanosheets, composed of nanoscale graphite-like carbon sheets, possess high electronic conductivity, short ion diffusion paths, large electrolyte contact area, and abundant accessible active sites, which are beneficial for improving lithium-ion storage capacity and rate performance. Furthermore, by constructing defect structures, controlling pore structures, and introducing heteroatoms such as nitrogen, the electronic structure and lithium-ion adsorption behavior of carbon materials can be further improved, providing additional lithium storage sites and thus overcoming the capacity limitations of the traditional single lithium intercalation mechanism of graphite. Therefore, nitrogen-doped two-dimensional carbon nanosheets are considered a class of high-performance lithium-ion battery anode materials with promising applications.

[0005] Existing methods for preparing two-dimensional carbon materials mainly include top-down exfoliation and bottom-up construction. Top-down methods typically obtain carbon nanosheets from graphitic materials through physical exfoliation, chemical redox reactions, ball milling, or electrochemical exfoliation. While these methods can achieve relatively thin sheet structures, they suffer from low yields, poor structural controllability, and high processing costs. Furthermore, the resulting materials primarily rely on graphitized structures for lithium intercalation for energy storage, limiting the potential for capacity improvement. In contrast, bottom-up methods construct two-dimensional carbon materials through the assembly, deposition, and carbonization of molecular precursors or gaseous carbon sources on a template surface. This approach offers greater flexibility in controlling the thickness, pore structure, defects, and heteroatom doping of carbon nanosheets.

[0006] In bottom-up methods for constructing two-dimensional carbon materials, the template method is a commonly used strategy. Soft template methods can construct relatively regular two-dimensional carbon structures, but template molecules are usually complex to prepare and costly, hindering large-scale applications. Hard template methods can utilize inorganic sheet materials or porous materials to achieve morphology guidance, but subsequent etching with strong acids or bases is often required to remove the template, increasing process steps and environmental burden, and potentially damaging the carbon material structure. Graphitic carbon nitride (g-C3N4) possesses characteristics such as sheet structure, high nitrogen content, wide availability, and self-decomposition at high temperatures, making it suitable as a two-dimensional morphology-guided template, self-sacrificing support, and nitrogen source, providing a new approach for constructing nitrogen-doped two-dimensional carbon materials. However, existing methods for preparing carbon nanosheets using g-C3N4 mostly use traditional carbon sources such as glucose, dopamine, and pitch as precursors, often requiring complex precursor adsorption, assembly, or post-processing. The efficient utilization of low-cost solid waste carbon sources still requires further development.

[0007] On the other hand, plastic waste is a potential carbon resource that is widely available, high in carbon content, and inexpensive. Low-density polyethylene (LDPE), in particular, is widely used in daily life and laboratory consumables; improper disposal after disposal can lead to resource waste and environmental burden. Converting waste LDPE into high-value-added carbon materials not only contributes to the resource utilization of waste plastics but also provides a low-cost carbon source for the preparation of advanced energy storage carbon materials. Existing methods for producing carbon from plastic pyrolysis typically rely on closed or pressurized reactors to limit the release of pyrolysis volatiles and promote secondary carbonization. However, these methods require sophisticated equipment, are complex to operate, and make it difficult to accurately construct carbon nanomaterials with two-dimensional sheet morphologies.

[0008] Therefore, how to effectively utilize the hydrocarbon-containing volatiles generated from the pyrolysis of waste LDPE under normal pressure, and how to achieve carbon nanosheet growth, in-situ nitrogen doping, and pore structure construction using self-removable two-dimensional templates, is an urgent problem to be solved in the high-value utilization of waste plastics and the preparation of high-performance lithium-ion battery anode materials. Developing a method for the controllable preparation of nitrogen-doped porous carbon nanosheets without pressurized reactors, metal catalysts, strong acid / base etching, or complex post-processing is of great significance for reducing preparation costs, simplifying processes, and improving the performance of lithium-ion battery anode materials. Summary of the Invention

[0009] The purpose of this invention is to overcome the shortcomings of existing technologies, such as the complex preparation process of two-dimensional carbon materials, the environmentally unfriendly template removal, the difficulty in effectively fixing carbon through plastic pyrolysis and volatilization, and the difficulty in constructing carbon nanosheets with controllable structures under normal pressure. This invention provides a method for preparing nitrogen-doped porous carbon nanosheets by using waste low-density polyethylene (LDPE) as a carbon source and graphitic carbon nitride (g-C3N4) as a multifunctional growth platform, taking advantage of the difference in thermal decomposition temperature range between waste LDPE and g-C3N4 through temperature gradient pyrolysis at normal pressure.

[0010] The core idea of ​​this invention is to utilize the different thermal decomposition temperature ranges of waste LDPE and g-C3N4, and to regulate the LDPE pyrolysis, carbon deposition, g-C3N4 self-sacrificial decomposition, and pore structure construction processes through segmented atmospheric pressure temperature gradient pyrolysis. Specifically, LDPE preferentially pyrolyzes in the range of approximately 450–500 °C to generate hydrocarbon-containing volatiles; before the g-C3N4 sheet structure is completely decomposed, the LDPE pyrolysis products can be deposited and carbonized in situ on its surface, gradually forming a carbon layer; as the temperature is further increased and maintained, g-C3N4 gradually undergoes self-sacrificial decomposition, which on the one hand removes the template, and on the other hand provides an in-situ nitrogen source and releases gas to promote pore structure formation, ultimately obtaining nitrogen-doped carbon nanosheets with a two-dimensional sheet morphology, nitrogen-containing defects, and a hierarchical mesoporous structure.

[0011] To achieve the above objectives, the present invention provides the following technical solution: A method for preparing nitrogen-doped carbon nanosheets for lithium-ion battery anodes by atmospheric pressure temperature gradient pyrolysis of waste low-density polyethylene involves mixing g-C3N4 powder and waste LDPE powder at a mass ratio of 1:(1~10); placing the mixture in a tube furnace and pyrolyzing it at 5 °C for 5 min under atmospheric pressure and a nitrogen atmosphere. -1 The heating rate was adjusted so that the temperature was first raised to 500 °C and held for 1 min, then raised to 700 °C and held for 1 h, and finally raised to 800 °C and held for 2 h. The product was then naturally cooled to room temperature under an inert atmosphere to obtain a black solid product, namely nitrogen-doped carbon nanosheets.

[0012] Furthermore, the waste LDPE powder is obtained through the following raw material pretreatment process: Waste LDPE plastic is selected, preferably waste laboratory wash bottles. After cleaning, drying, shearing, crushing and passing through a 100-mesh sieve, waste LDPE powder with a particle size of <150 μm is obtained.

[0013] Furthermore, the g-C3N4 powder is obtained through the following raw material pretreatment process: Melamine was placed in a covered crucible and heated in a muffle furnace under air atmosphere at 10 °C for 1 min. -1 The temperature was raised to 550 ℃ and held for 3 h. After natural cooling, the powder was ground to obtain g-C3N4 powder.

[0014] As a preferred embodiment, g-C3N4 powder and waste LDPE powder are mixed at a mass ratio of 1:5, and the resulting product is denoted as nitrogen-doped carbon nanosheets NCNS-5.

[0015] The nitrogen-doped carbon nanosheets prepared by the above method are used as negative electrode active materials in lithium-ion batteries.

[0016] Preferably, the nitrogen-doped porous carbon nanosheet active material, polyvinylidene fluoride and conductive carbon black are uniformly mixed in a mass ratio of 7:2:1, and an appropriate amount of N-methyl-2-pyrrolidone is added to prepare a uniform slurry. The obtained slurry is uniformly coated on a copper foil current collector, vacuum dried at 80 °C for 10 h, and then punched to obtain a negative electrode sheet.

[0017] Furthermore, using the obtained negative electrode as the working electrode, a lithium metal sheet as the counter electrode, and a Celgard 2400 polypropylene membrane as the separator, a 1 mol L... -1 A LiPF6 EC / DEC mixed solution was used as the electrolyte, and CR2016 coin cells were assembled in an inert atmosphere glove box.

[0018] The nitrogen-doped carbon nanosheets NCNS-5 prepared by the above method were used as a negative electrode in the assembly of NCNS-5 / / NCM111 full cells.

[0019] The beneficial effects of this invention are: 1. This invention provides a method for preparing nitrogen-doped carbon nanosheets by atmospheric pressure temperature gradient pyrolysis of waste LDPE. This method utilizes the different thermal decomposition temperature ranges of LDPE and g-C3N4 to achieve segmented synergistic coupling of the deposition and carbonization of LDPE pyrolysis volatiles and the self-sacrificial decomposition of g-C3N4. Unlike simply using g-C3N4 as a physical template, this invention first causes LDPE to pyrolyze to form hydrocarbon-containing volatiles by short-term holding at 500 °C, then deposits and carbonizes the gaseous products in situ at 700 °C before the complete decomposition of the g-C3N4 sheet structure, and finally performs self-sacrificial decomposition of g-C3N4 at 800 °C. This method simultaneously achieves template removal, in-situ nitrogen doping, and pore structure construction, thereby realizing the conversion of waste LDPE pyrolysis products into carbon materials under atmospheric pressure. This process avoids the dependence on closed or pressurized reaction equipment in traditional plastic pyrolysis carbon production; and it requires no metal catalysts, external nitrogen sources, activation treatment, or post-purification treatment, resulting in a shorter process flow and better environmental friendliness.

[0020] 2. This invention provides a new technical path for the high-value utilization of waste LDPE. Waste LDPE is widely available, has a high carbon content, and is inexpensive. Using the method of this invention, low-value plastic waste can be transformed into nitrogen-doped carbon nanosheet materials with energy storage application value, which is conducive to realizing the resource utilization of waste plastics and reducing the preparation cost of high-performance carbon-based anode materials.

[0021] 3. The nitrogen-doped porous carbon nanosheets prepared by this invention possess structural features suitable for rapid lithium-ion storage. The preferred sample NCNS-5 exhibits a relatively complete two-dimensional sheet structure with a sheet thickness of approximately 4.97 nm, possessing high pore volume, moderate specific surface area, and abundant mesoporous structure; simultaneously, nitrogen-doped defect sites and sp... 2 / sp 3 Hybrid carbon frameworks are beneficial for improving lithium-ion adsorption capacity, shortening ion transport paths, promoting electrolyte wetting, and enhancing electrode reaction kinetics.

[0022] 4. The material obtained in this invention exhibits excellent electrochemical performance as a negative electrode material for lithium-ion batteries. The preferred sample NCNS-5 demonstrates high reversible capacity and cycle stability in half-cells, at 1.0 A g. -1 It retains approximately 436 mAh g after 1000 cycles at current density. -1 The reversible capacity; when assembled into a full cell with a commercial NCM111 cathode, the energy density, calculated based on the total mass of the positive and negative electrode active materials, is approximately 356 Wh kg. -1 This indicates that the nitrogen-doped porous carbon nanosheets prepared by this invention have good prospects for practical applications. Attached Figure Description

[0023] The accompanying drawings, which form part of this specification, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an undue limitation of the invention. Wherein: Figure 1 This is a schematic diagram of the process for preparing nitrogen-doped porous carbon nanosheets (NCNS) by segmented heating at 500 ℃, 700 ℃ and 800 ℃ under normal pressure nitrogen atmosphere according to the present invention.

[0024] Figure 2 The thermogravimetric analysis curves of LDPE, g-C3N4 and g-C3N4 / LDPE blend precursors in this invention are shown.

[0025] The following are morphological and structural characterization images of the nitrogen-doped porous carbon nanosheets in this invention: Figure 3 This is a scanning electron microscope (SEM) image of NCNS-1 in this invention; Figure 4 This is a scanning electron microscope (SEM) image of NCNS-5 in this invention; Figure 5 This is a scanning electron microscope (SEM) image of NCNS-10 in this invention; Figure 6 This is a transmission electron microscope (TEM) image of NCNS-5 in this invention; Figure 7 This is a high-resolution transmission electron microscope (HRTEM) image of NCNS-5 in this invention; Figure 8 This is a thickness analysis diagram of the NCNS-5 atomic force microscope (AFM) in this invention.

[0026] Figure 9 The diagram shows the pore structure characterization of nitrogen-doped porous carbon nanosheets in this invention, including (a) N2 adsorption-desorption isotherms and (b) pore size distribution curves.

[0027] The following are half-cell electrochemical performance figures when nitrogen-doped porous carbon nanosheets are used as the anode material for lithium-ion batteries in this invention: Figure 10 The cyclic voltammetry curve for NCNS-5; Figure 11 The initial constant current charge-discharge curves for NCNS-1, NCNS-5, and NCNS-10; Figure 12 The constant current charge-discharge curves for the first three cycles of NCNS-5; Figure 13 Rate performance curves for NCNS-1, NCNS-5, and NCNS-10; Figure 14 For NCNS-1, NCNS-5 and NCNS-10 at 0.5 A g-1 The following is a cycle performance curve; Figure 15 For NCNS-1, NCNS-5 and NCNS-10 at 1.0A g -1 The following is a cycle performance curve; Figure 16 This is a comparison chart of cycle performance.

[0028] The following are electrochemical performance figures of a lithium-ion full cell assembled using NCNS-5 as the negative electrode and commercial NCM111 as the positive electrode according to this invention: Figure 17 A schematic diagram of the NCNS-5 / / NCM111 full cell structure; Figure 18 Cyclic voltammetry curves at different scan rates; Figure 19 0.4 mV s -1 The first three cycles of cyclic voltammetry curves; Figure 20 The constant current charge-discharge curves for the first three cycles; Figure 21 This is the rate performance curve; Figure 22 0.5 A g -1 The following is a cycle performance curve. Detailed Implementation

[0029] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention are within the scope of protection of the present invention.

[0030] This invention provides a method for preparing nitrogen-doped carbon nanosheets for lithium-ion battery anodes by atmospheric pressure temperature gradient pyrolysis of waste low-density polyethylene, comprising the following steps: a. Raw material pretreatment: Waste low-density polyethylene (LDPE) material is selected and subjected to washing, drying, shearing or crushing, pulverizing and sieving to obtain waste LDPE powder with a particle size <150 µm, which is used as a carbon source. Preferably, the waste low-density polyethylene (LDPE) material is waste laboratory wash bottles.

[0031] Melamine was placed in a crucible and heated for polycondensation in air. After cooling, it was ground to obtain g-C3N4 powder. Preferably, the heating polycondensation was carried out in a muffle furnace at 10 °C for [time missing]. -1 Heat to 550 ℃ and keep warm for 3 hours.

[0032] b. Precursor mixing: The waste LDPE powder obtained in step a is mixed with g-C3N4 powder at a set mass ratio and then ground thoroughly in an agate mortar to ensure uniform contact between the two; thus, a g-C3N4 / LDPE blend precursor is obtained.

[0033] Furthermore, the mass ratio of g-C3N4 / LDPE is 1:(1~10) (e.g., 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10).

[0034] c. Atmospheric pressure temperature gradient pyrolysis: The blended precursor is placed in a crucible or corundum boat and covered to prolong the residence time of volatiles near the precursor. It is then placed in a tube furnace and subjected to segmented temperature gradient pyrolysis under an inert atmosphere at atmospheric pressure. At 5 ℃ min -1 The heating rate was adjusted so that the temperature was first raised to 500 °C in the LDPE pyrolysis temperature zone and held for 1 min, so that LDPE would preferentially pyrolyze to form hydrocarbon-containing volatiles. The temperature was raised to 700 °C and held for 1 h to allow LDPE pyrolysis products to be deposited and carbonized in situ on the surface of g-C3N4 sheets that were not yet fully decomposed. Finally, the temperature was raised to 800 °C and held for 2 h to allow g-C3N4 to gradually decompose by self-sacrifice, while simultaneously achieving template removal, in-situ nitrogen doping, and pore structure formation. After pyrolysis, the material is naturally cooled to room temperature under an inert atmosphere, and the black solid product is collected directly to obtain nitrogen-doped porous carbon nanosheets. No acid washing, alkali washing, catalyst removal, external nitrogen source doping, activation treatment, or other complex post-treatments are required.

[0035] d. Negative electrode preparation and battery assembly: The nitrogen-doped porous carbon nanosheets obtained in step c are mixed with binder and conductive agent to form a slurry, which is then coated onto a copper foil current collector. After drying and punching, a lithium-ion battery negative electrode sheet is obtained. The obtained negative electrode sheet is then assembled with a separator, electrolyte and counter electrode to form a lithium-ion battery half cell or full cell.

[0036] Specifically, the prepared nitrogen-doped porous carbon nanosheet active material, polyvinylidene fluoride (PVDF), and conductive carbon black were uniformly mixed at a mass ratio of 7:2:1, and an appropriate amount of N-methyl-2-pyrrolidone (NMP) was added to prepare a uniform slurry. The slurry was uniformly coated onto a copper foil current collector and then vacuum dried at 80 °C for 10 h. The dried electrode was then punched to obtain a circular working electrode with a diameter of 14 mm. The active material loading of the working electrode was controlled to be 0.6~0.8 mg cm⁻¹. -2The assembly of the CR2016 coin cell was completed in an argon atmosphere glove box with water and oxygen concentrations both below 0.1 ppm. The electrochemical system used lithium foil as the counter electrode and a Celgard 2400 polypropylene membrane as the separator, with a 1 mol L... -1 A mixed solution of LiPF6 EC / DEC (volume ratio 1:1) was used as the electrolyte. Constant current charge-discharge and cycle performance evaluation were performed in the voltage range of 0.01~3.0 V using a Neware BTS-4000 charge-discharge tester. Electrochemical impedance spectroscopy (EIS) and cyclic voltammetry (CV) tests were performed on a CHI660E electrochemical workstation.

[0037] The present invention will now be described in detail with reference to embodiments. It should be noted that, unless otherwise specified, the embodiments and features described in the embodiments of the present invention can be combined with each other.

[0038] Example 1 Discarded laboratory low-density polyethylene (LDPE) wash bottles were used as a representative source of waste plastics. They were thoroughly cleaned with deionized water and ethanol to remove surface contaminants, dried, cut into small pieces, crushed, and passed through a 100-mesh sieve to obtain waste LDPE powder, which was then used as a carbon source.

[0039] Weigh analytical grade melamine into a covered crucible, place the crucible in a muffle furnace, and incubate at 10°C for 1 minute in air atmosphere. -1 The temperature was increased to 550 °C at a heating rate and held at 550 °C for 3 h. After the muffle furnace cooled naturally to room temperature, the resulting pale yellow solid was removed and ground into powder to obtain graphitic carbon nitride g-C3N4, which served as a two-dimensional growth platform, self-sacrificing template, and in-situ nitrogen source in the subsequent pyrolysis process.

[0040] The obtained g-C3N4 powder was added to an agate mortar at a 1:1 mass ratio with waste LDPE powder and ground thoroughly until homogeneous, yielding g-C3N4 / LDPE blend precursors with different ratios. The resulting blend precursors were then placed in covered porcelain crucibles or corundum boats and placed in a tube furnace. Under a nitrogen atmosphere at atmospheric pressure, the mixture was heated at 5 °C for 1 minute. -1 Atmospheric temperature gradient pyrolysis was performed at the following heating rate: first, the temperature was raised to 500 °C and held for 1 min, then raised to 700 °C and held for 1 h, and finally raised to 800 °C and held for 2 h. After the system cooled naturally to room temperature, the resulting black solid product was collected directly without further processing and designated as NCNS-1.

[0041] Example 2 Discarded laboratory low-density polyethylene (LDPE) wash bottles were used as a representative source of waste plastics. They were thoroughly cleaned with deionized water and ethanol to remove surface contaminants, dried, cut into small pieces, crushed, and passed through a 100-mesh sieve to obtain waste LDPE powder, which was then used as a carbon source.

[0042] Weigh analytical grade melamine into a covered crucible, place the crucible in a muffle furnace, and incubate at 10°C for 1 minute in air atmosphere. -1 The temperature was increased to 550 °C at a heating rate and held at 550 °C for 3 h. After the muffle furnace cooled naturally to room temperature, the resulting pale yellow solid was removed and ground into powder to obtain graphitic carbon nitride g-C3N4, which served as a two-dimensional growth platform, self-sacrificing template, and in-situ nitrogen source in the subsequent pyrolysis process.

[0043] The obtained g-C3N4 powder was added to an agate mortar at a mass ratio of 1:5 with waste LDPE powder and ground thoroughly until uniformly mixed to obtain g-C3N4 / LDPE blend precursors with different ratios. The resulting blend precursors were then placed in covered porcelain crucibles or corundum boats and placed in a tube furnace. Under a nitrogen atmosphere at atmospheric pressure, the mixture was heated at 5 °C for 1 minute. -1 Atmospheric temperature gradient pyrolysis was performed at the following heating rate: first, the temperature was raised to 500 °C and held for 1 min, then raised to 700 °C and held for 1 h, and finally raised to 800 °C and held for 2 h. After the system cooled naturally to room temperature, the resulting black solid products were collected directly without further processing and designated as NCNS-5.

[0044] During the aforementioned pyrolysis process, LDPE preferentially decomposes and releases hydrocarbon-containing volatiles in the approximately 450–500 °C range. At this temperature, the g-C3N4 sheet structure is not yet fully decomposed, providing a two-dimensional growth platform for the deposition and in-situ carbonization of LDPE decomposition products. As the temperature further increases, g-C3N4 gradually undergoes self-sacrificial decomposition, particularly intensified at higher temperatures, thereby simultaneously achieving template removal, in-situ nitrogen doping, and pore structure construction, resulting in nitrogen-doped porous carbon nanosheet materials. This process does not require a pressurized reactor, external catalyst, external nitrogen source, activation treatment, or subsequent template removal steps, simplifying the process flow.

[0045] Example 3 Discarded laboratory low-density polyethylene (LDPE) wash bottles were used as a representative source of waste plastics. They were thoroughly cleaned with deionized water and ethanol to remove surface contaminants, dried, cut into small pieces, crushed, and passed through a 100-mesh sieve to obtain waste LDPE powder, which was then used as a carbon source.

[0046] Weigh analytical grade melamine into a covered crucible, place the crucible in a muffle furnace, and incubate at 10°C for 1 minute in air atmosphere. -1The temperature was increased to 550 °C at a heating rate and held at 550 °C for 3 h. After the muffle furnace cooled naturally to room temperature, the resulting pale yellow solid was removed and ground into powder to obtain graphitic carbon nitride g-C3N4, which served as a two-dimensional growth platform, self-sacrificing template, and in-situ nitrogen source in the subsequent pyrolysis process.

[0047] The obtained g-C3N4 powder was added to an agate mortar at a mass ratio of 1:10 with waste LDPE powder and ground thoroughly until uniformly mixed to obtain g-C3N4 / LDPE blend precursors with different ratios. The resulting blend precursors were then placed in covered porcelain crucibles or corundum boats and placed in a tube furnace. Under a nitrogen atmosphere at atmospheric pressure, the mixture was heated at 5 °C for 1 minute. -1 Atmospheric temperature gradient pyrolysis was performed at the following heating rate: first, the temperature was raised to 500 °C and held for 1 min, then raised to 700 °C and held for 1 h, and finally raised to 800 °C and held for 2 h. After the system cooled naturally to room temperature, the resulting black solid products were collected directly without further processing and designated as NCNS-10.

[0048] Experimental Example 1 Morphological and pore structure characterization were performed on NCNS-1, NCNS-5 and NCNS-10 obtained in Examples 1 to 3 above.

[0049] (a) Morphological characteristics like Figures 3-5 As shown, scanning electron microscopy results indicate that the mass ratio of g-C3N4 / LDPE has a significant impact on the morphology of the obtained carbon materials: insufficient carbon source supply in NCNS-1 results in an indistinct sheet structure; excessive LDPE content in NCNS-10 leads to thicker carbon sheets that are easily stacked; and when the mass ratio of g-C3N4 / LDPE is 1:5, the obtained NCNS-5 exhibits a more complete two-dimensional carbon nanosheet structure.

[0050] like Figure 6 The transmission electron microscope image shown and as follows Figure 7 The high-resolution transmission electron microscope image shown further demonstrates that NCNS-5 is an ultrathin, wrinkled nanosheet structure with typical characteristics of two-dimensional materials. Figure 7 High-resolution images reveal clear lattice fringes, indicating that the sample is a composite carbon structure with both crystalline and amorphous phases. The images also show obvious nanopores; the discontinuous lattice regions and porous structure together endow the material with abundant structural defects, which can provide sufficient active sites, facilitating electrochemical reactions. The inset shows a lattice fringes spacing of 0.363 nm, matching the interplanar spacing of graphite (002), further supporting the existence of a graphite-like crystalline phase.

[0051] like Figure 8As shown, atomic force microscopy tests revealed that the sheet thickness of NCNS-5 was approximately 4.97 nm, indicating that this method can effectively prepare ultrathin carbon nanosheet materials.

[0052] (ii) Characterization of pore structure Nitrogen adsorption-desorption test results show that the obtained NCNS material has mesoporous structure characteristics. Its specific surface area and pore structure parameters are shown in Table 1. The N2 adsorption-desorption curves and pore size distribution are shown in... Figure 9 As shown. The specific surface area of ​​NCNS-5 is approximately 448.3 m². 2 g -1 The total pore volume is approximately 2.148 cm³. 3 g -1 The pore size is mainly distributed in the range of 3 to 36 nm, indicating that it has a high contactable surface area and a relatively rich pore structure, which is beneficial to electrolyte wetting and lithium ion transport.

[0053] Table 1. Specific surface area and pore structure parameters of NCNS

[0054] Experimental Example 2 The nitrogen-doped carbon nanosheets prepared in Examples 1-3 were used as negative electrode active materials in lithium-ion batteries, and their electrical performance was tested.

[0055] (i) The obtained NCNS-1, NCNS-5, and NCNS-10 were used as negative electrode active materials for lithium-ion batteries, respectively, and mixed with polyvinylidene fluoride (PVDF) and conductive carbon black at a mass ratio of 7:2:1. An appropriate amount of N-methyl-2-pyrrolidone (NMP) was added to prepare a uniform slurry. The slurry was uniformly coated onto a copper foil current collector and then vacuum dried at 80 °C for 10 h. The dried electrode was punched to obtain a circular working electrode with a diameter of 14 mm. The active material loading of the working electrode was controlled to be 0.6~0.8 mg cm⁻¹. -2 The assembly of the CR2016 coin cell was completed in an argon atmosphere glove box with water and oxygen concentrations both below 0.1 ppm. The electrochemical system used lithium foil as the counter electrode and a Celgard 2400 polypropylene membrane as the separator, with a 1 mol L... -1 A LiPF6 EC / DEC mixed solution (volume ratio 1:1) was used as the electrolyte. Constant current charge-discharge and cycle performance evaluation were performed using a Neware BTS-4000 charge-discharge tester within a voltage range of 0.01–3.0 V. Electrochemical impedance spectroscopy (EIS) and cyclic voltammetry (CV) tests were performed on a CHI660E electrochemical workstation.

[0056] The electrical performance test results are as follows: like Figure 11 The first constant current charge-discharge curves of NCNS-1, NCNS-5 and NCNS-10 are shown. Among them, NCNS-5 has the highest first-cycle discharge capacity, but the first-cycle coulombic efficiency is low, which is a typical characteristic of carbon-based materials (the formation of the SEI film consumes the lithium source).

[0057] like Figure 13 The rate performance curves of NCNS-1, NCNS-5, and NCNS-10 are shown. Among them, NCNS-1 has the lowest capacity, and NCNS-10 is in the middle, indicating that nitrogen content and structure have a significant impact on rate performance. NCNS-5 has the best rate performance, and its unique nanoporous structure and ultrathin morphology are conducive to rapid lithium-ion transport.

[0058] like Figure 14 The NCNS-1, NCNS-5, and NCNS-10 shown are at 0.5 A g. -1 The cycling performance curves at 0.5 A g show that NCNS-5 exhibits good performance at 0.5 A g. -1 It exhibited excellent cycle stability.

[0059] like Figure 15 The NCNS-1, NCNS-5, and NCNS-10 shown are at 1.0 A g. -1 Cyclic performance curves of NCNS-5 at 1.0 A g; -1 It maintains excellent performance even after 1000 long cycles, proving its excellent structural stability and electrochemical durability.

[0060] Therefore, NCNS-5 exhibits the best performance as a negative electrode active material for lithium-ion batteries. Furthermore, as... Figure 10 The cyclic voltammetry curves of NCNS-5 show that NCNS-5 exhibits good electrochemical reversibility, with the initial irreversible capacity primarily originating from SEI film formation. Figure 12 The NCNS-5 constant current charge-discharge curves for the first three cycles shown illustrate that NCNS-5 exhibits excellent electrochemical reversibility starting from the second cycle. The irreversible capacity in the first cycle mainly originates from SEI film formation and surface functional group reactions. Figure 16 The comparison chart of cycling performance shown illustrates that the electrochemical performance of NCNS-5 is superior to or comparable to that of a variety of advanced anode materials reported in the current literature (the comparison materials in the chart include CN-Ni-800, GNC, MnO2, FeS2, GPCS, 2D-PNC, SnO2@AC, SnS2@NC, etc.), and has practical application potential.

[0061] Electrochemical testing results showed that all three materials possessed a certain degree of reversible lithium storage capacity. Among them, NCNS-5, due to its more complete two-dimensional layered structure, suitable nitrogen doping level, and abundant mesoporous structure, exhibited superior rate performance and cycle stability. (At 0.05 A g...) -1 At current density, NCNS-5 achieves an initial reversible capacity of 807 mAh g. -1 ; at 0.5 A g -1 The capacity can still be maintained at approximately 736 mAh g after 500 cycles. -1 , at 1.0 Ag -1 The capacity can still be maintained at approximately 436 mAh g after 1000 cycles. -1 This indicates that it has good high-rate lithium storage capacity and cycle stability.

[0062] (ii) Assemble a lithium-ion full battery using NCNS-5 as the negative electrode and commercial NCM111 as the positive electrode, such as Figure 17 As shown, a typical lithium-ion battery full-cell configuration is illustrated, where NCM111 provides the lithium source and capacity, and NCNS-5 serves as the high-capacity anode. The electrochemical performance of the NCNS-5 / / NCM111 full cell was verified, and the results are as follows: like Figure 18 The cyclic voltammetry curves at different scan rates show that the full cell operating voltage plateau is approximately 3.3-3.7 V, which is suitable for practical applications; the small peak potential difference indicates low polarization and good reversibility of the electrochemical reaction; as the scan rate increases, the polarization increases but still maintains a clear peak shape, indicating that the material has good rate response capability.

[0063] like Figure 19 The figure of 0.4 mV s is shown. -1 The following three cyclic voltammetry curves illustrate that the NCNS-5 / / NCM111 full cell exhibits excellent electrochemical reversibility starting from the second cycle, and the SEI film is basically stable in the first cycle.

[0064] like Figure 20 The constant current charge-discharge curves shown for the first three cycles illustrate that there is a small amount of irreversible capacity in the first cycle (SEI film stabilization), but the coulombic efficiency rapidly approaches 100% after the second cycle, and the stable voltage plateau indicates that the full cell has good operating voltage stability.

[0065] like Figure 21 The rate performance curves shown illustrate that the NCNS-5 / / NCM111 full cell performs well at high rates (1.0 A g). -1 There is still ~400 mAh g -1 This indicates that lithium-ion diffusion and electron transport efficiency are good, proving that the electrode structure is stable.

[0066] like Figure 22 The 0.5 A g shown -1 The NCNS-5 / / NCM111 full cell exhibits excellent cycle stability according to the cycle performance curves, proving that the full cell has practical power supply capability and application potential.

[0067] The above results indicate that, based on the total mass of the positive and negative electrode active materials, its mass energy density is approximately 356 Wh kg. -1 This demonstrates that the nitrogen-doped porous carbon nanosheets prepared by this invention are suitable for high-performance lithium-ion battery anode materials.

[0068] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A method for preparing nitrogen-doped carbon nanosheets for lithium-ion battery anodes by atmospheric pressure temperature gradient pyrolysis of waste low-density polyethylene, characterized in that, G-C3N4 powder and waste LDPE powder were mixed evenly at a mass ratio of 1:(1~10); the mixture was placed in a tube furnace and heated at 5 °C for 1 minute under a nitrogen atmosphere at atmospheric pressure. -1 The heating rate was as follows: first, the temperature was raised to 500 °C and held for 1 min, then raised to 700 °C and held for 1 h, and finally raised to 800 °C and held for 2 h. After natural cooling to room temperature under an inert atmosphere, a black solid product was obtained directly, which is nitrogen-doped carbon nanosheets.

2. The method as described in claim 1, characterized in that, The waste LDPE powder is obtained through the following raw material pretreatment process: Waste LDPE plastic was selected, and after washing, drying, shearing, crushing and passing through a 100-mesh sieve, waste LDPE powder with a particle size of <150μm was obtained.

3. The method as described in claim 1, characterized in that, The g-C3N4 powder is obtained through the following raw material pretreatment process: Melamine was placed in a covered crucible and heated in a muffle furnace under air atmosphere at 10 °C for 1 min. -1 The temperature was raised to 550 ℃ and held for 3 h. After natural cooling, the powder was ground to obtain g-C3N4 powder.

4. The method according to any one of claims 1 to 3, characterized in that, g-C3N4 powder and waste LDPE powder are mixed in a mass ratio of 1:

5.

5. The nitrogen-doped carbon nanosheets prepared by the method described in claim 1 are used as negative electrode active materials in lithium-ion batteries.

6. The application method as described in claim 5, characterized in that, The nitrogen-doped porous carbon nanosheet active material, polyvinylidene fluoride and conductive carbon black were uniformly mixed in a mass ratio of 7:2:1, and an appropriate amount of N-methyl-2-pyrrolidone was added to prepare a uniform slurry. The obtained slurry was uniformly coated on a copper foil current collector and vacuum dried at 80 °C for 10 h. Then, the negative electrode sheet was punched to obtain the negative electrode sheet.

7. The application method as described in claim 6, characterized in that, Using the obtained negative electrode as the working electrode, a lithium metal sheet as the counter electrode, and a Celgard 2400 polypropylene membrane as the separator, 1 mol L... -1 A LiPF6 EC / DEC mixed solution was used as the electrolyte, and CR2016 coin cells were assembled in an inert atmosphere glove box.

8. The nitrogen-doped carbon nanosheets NCNS-5 prepared by the method described in claim 4 are used as a negative electrode in the assembly of NCNS-5 / / NCM111 full cells.